2016
DOI: 10.3389/fpsyg.2016.00088
|View full text |Cite
|
Sign up to set email alerts
|

Designed Natural Spaces: Informal Gardens Are Perceived to Be More Restorative than Formal Gardens

Abstract: Experimental research shows that there are perceived and actual benefits to spending time in natural spaces compared to urban spaces, such as reduced cognitive fatigue, improved mood, and reduced stress. Whereas past research has focused primarily on distinguishing between distinct categories of spaces (i.e., nature vs. urban), less is known about variability in perceived restorative potential of environments within a particular category of outdoor spaces, such as gardens. Conceptually, gardens are often consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Studies have shown that various variables modify the relationship between natural environments and SWB, such as the quality of green space [118,119], biodiversity/variation in vegetation types [120][121][122], untended or poorly managed green space conditions [32,123,124], types of activities available [7], the degree of crowding [122], the degree of naturalness [124,125], proximity to green space [126], accessibility [125], and perceived sense of safety [127].…”
Section: Effects Of Frequency Of Visits and Time Spent In Ugs On Swbmentioning
confidence: 99%
“…Studies have shown that various variables modify the relationship between natural environments and SWB, such as the quality of green space [118,119], biodiversity/variation in vegetation types [120][121][122], untended or poorly managed green space conditions [32,123,124], types of activities available [7], the degree of crowding [122], the degree of naturalness [124,125], proximity to green space [126], accessibility [125], and perceived sense of safety [127].…”
Section: Effects Of Frequency Of Visits and Time Spent In Ugs On Swbmentioning
confidence: 99%
“…Several studies, indeed, have investigated the restorative potential of nature through a comparison between pleasant natural environments and unpleasant built environments (Purcell et al, 2001; Berto, 2005). In this regard, some authors have shown the role of perceived attractiveness, or similar concepts, in the restoration process (Dijkstra et al, 2008; Nasar and Terzano, 2010; Twedt et al, 2016). On the other hand, the study of the restorative potential of built environments is still scant, and referred to examples with historical and/or artistic value, such as museums, monasteries, renewed and attractive neighborhoods, and plazas (Kaplan et al, 1993; Scopelliti and Giuliani, 2004, 2005; Ouellette et al, 2005; Karmanov and Hamel, 2008; Abdulkarim and Nasar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is clearly the case for landscaped gardens in particular starting with the Italian Renaissance style (Leon Battista Alberti, 1404–1472, wrote a book about architecture that talks extensively about gardens). A recent study, however, has found that the restorative power of gardens was higher for informal rather than formal gardens (Twedt, Rainey & Proffitt, 2016).…”
Section: Resultsmentioning
confidence: 98%